2012
DOI: 10.1002/aqc.1241
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the diet of a recovering Eurasian otter population between the 1970s and 2010

Abstract: ABSTRACT1. Diet is an essential element for understanding how the Eurasian otter (Lutra lutra) is re-colonizing its former range in England following a population decline observed in the 1950s to 1970s.2. Otter spraints from the River Glaven catchment (north Norfolk, eastern England) were collected seasonally between 2009 and 2010 from three habitat types (ponds, 'retenus' (small in-stream reservoirs), and stream stretches). Feeding tactics of the otter were compared between habitat types and, using previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
86
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(98 citation statements)
references
References 30 publications
(45 reference statements)
10
86
1
Order By: Relevance
“…It was unclear whether the results of this study reflected a high abundance of common bullheads in the environment or if otters were preferentially selecting bullheads, because the EA does not quantify their abundance. However, several other dietary studies have also found a large number of bullheads in otter diet (see Copp and Roche 2003), with some noting preferential selection (Almeida et al 2012). Cote et al (2008) also found a preference for slow-swimming marine cottids in North American river otters.…”
Section: Evidence For Prey Selection By Ottersmentioning
confidence: 93%
See 3 more Smart Citations
“…It was unclear whether the results of this study reflected a high abundance of common bullheads in the environment or if otters were preferentially selecting bullheads, because the EA does not quantify their abundance. However, several other dietary studies have also found a large number of bullheads in otter diet (see Copp and Roche 2003), with some noting preferential selection (Almeida et al 2012). Cote et al (2008) also found a preference for slow-swimming marine cottids in North American river otters.…”
Section: Evidence For Prey Selection By Ottersmentioning
confidence: 93%
“…Since then, otter populations have slowly recovered; the most recent survey shows that, in England, otters are present at 56.3 % of 3327 sites surveyed (Crawford 2010). However, as otters continue to recolonize British waterways, there is growing concern amongst some sectors of the angling and fish-farming community that otter predation will impact fish populations, both in rivers and artificial stillwaters (Almeida et al 2012;Scholey 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At freshwater aquaculture sites across Europe, conflicts with piscivorous fauna, such as otter Lutra lutra have been widely reported (e.g., Kloskowski, 2005Kloskowski, , 2011. In freshwaters with less intensive management, such as ponds and rivers used for catch and release recreational angling, anglers frequently report fish losses to otter predation as a major concern, specifically for the loss of larger bodied fishes Almeida et al, 2012). Where dietary data are available, however, they suggest that these fishes are a minor component of their diet, with species including eel Anguilla anguilla and bullhead Cottus gobio more commonly taken (Britton et al, 2006;Grant and Harrington, 2015).…”
Section: Introductionmentioning
confidence: 99%